Collective Action in the Formation of Pre-Modern States - Blanton, Richard; Fargher, Lane.; SpringerLink (Online service) (New York, NY : Springer New York, 2008)
Collective Action in the Formation of Pre-Modern States by Richard Blanton and Lane Fargher Purdue University, West Lafayette, IN Research over the past half-century has substantially increased the quantity and quality of information on the evolution of early complex societies. New methods and new discoveries have inspired anthropological archaeologists and other social scientists to rethink prevailing theories, which now seem excessively deterministic and unable to account for the role of human action in social change. The authors propose that the rational choice theory of collective action, especially as it has been developed by political scientists, is a fruitful new direction for theory-building that can overcome these limitations. This theory addresses the dilemma faced by any group attempting to build a complex society, namely, that the rational and self-interested behavior of social actors may limit the potential for collective action and group solidarity. This book explores a collective action perspective on the formation of pre-modern states, but does not only promote a new mode of theoretical understanding. Rather, it subjects collective action theory to a methodologically rigorous evaluation using a systematic cross-cultural analysis of historical, ethnographic, and archaeological data drawn from a world-wide sample of societies. These data provide strong support for the theory while pointing the way to a more complex and nuanced approach to collective action, uniting theories of pre-modern and modern states.
Introduction The Rise and Demise of Neoevolutionist Theory -- The Theory of Collective Action as Applied to Pre-Modern States -- Historical Backgrounds to the Study Regions and the Coded Societies, Part I: Introduction and East Asia -- Background to State Formation and the Coded Polities in Southeast Asia -- Background to State Formation and the Coded Polities in South Asia and the Coded Polities -- Background to Sub-Saharan African State Formation -- Background to State Formation in Western Eurasia and the Mediterranean/North Africa -- Background to the New World States -- Material and Social Background to the Coded Societies of East Asia and Tibet -- Material and Social Background to the Coded Southeast Asian Societies -- Material and Social Background to the Coded Societies of South Asia -- Material and Social Background to the Coded African Societies -- Material and Social Background to the Coded Societies of West Eurasia and the Mediterranean/North Africa -- Material and Social Background to the New World Coded Societies -- A Method for Comparing Revenue Sources -- Public Goods -- Bureaucratization -- Modes of Control of the Behavior of Principals -- Main Results and Conclusions -- Conclusions, Part II: Collective Action in Relation to World-System, Region, and Community -- Final Reflections on Collective Action as an Approach to the Study of Pre-Modern States -- What is a (3z(BModern(3y (BState?s
Keywords: Social sciences; Political science; Anthropology; Archaeology; Social Sciences; Archaeology; Anthropology; Political Science; Electronic books